Orientin Reduces the Effects of Repeated Procedural Neonatal Pain in Adulthood: Network Pharmacology Analysis, Molecular Docking Analysis, and Experimental Validation - Dong-Dong Guo; Hai-Yan Huang; Hai-E. Liu; Kun Liu; Xing-Jing Luo (Pain Research and Management)
Background. Premature infants often undergo painful procedures and consequently experience repeated procedural neonatal pain. This can elicit hyperalgesia and cognitive impairment in adulthood. Treatments for neonatal pain are limited. Orientin is a flavonoid C-glycoside that has repeatedly been shown to have pharmacological effects in the past decades. The aim of this study was to systematically explore the effect of orientin on repeated procedural neonatal pain using network pharmacology, molecular docking analysis, and experimental validation. Methods. Several compound-protein databases and disease-protein databases were employed to identify proteins that were both predicted targets of orientin and involved in neonatal pain. A protein-protein interaction (PPI) network was constructed, and Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed to explore the potential mechanism of action. Molecular docking analysis was employed to calculate the binding energy and visualize the interactions between orientin and potential target proteins. Finally, a mouse model of repeated procedural neonatal pain was established and orientin was administered for 6 days. The mechanical and thermal pain thresholds were assessed in neonates and adult mice. A Morris water maze was employed to investigate cognitive impairment in adult mice. Results. A total of 286 proteins that were both predicted targets of orientin and involved in neonatal pain were identified. The hub proteins were SRC, HSP90AA1, MAPK1, RHOA, EGFR, AKT1, PTPN11, ESR1, RXRA, and HRAS. GO analysis indicated that the primary biological process (BP), molecular function (MF), and cellular component (CC) were protein phosphorylation, protein kinase activity, and vesicle lumen, respectively. KEGG analysis revealed that the mitogen-activated protein kinase (MAPK) signaling pathway may be the key to the mechanism of action. Molecular docking analysis showed the high binding affinities of orientin for MAPK1, MAPK8, and MAPK14. In mice, orientin inhibited the hyperalgesia in the pain threshold tests in neonates and adult mice and cognitive impairment in adult mice. Immunofluorescence showed that phosphorylated MAPK1 (p-ERK) protein levels in the hippocampus and spinal dorsal horn were downregulated by orientin. Conclusion. The findings suggested that orientin alleviates neonatal pain, and the MAPK signaling pathway is involved.